Harmonic model validation of power generation units. Issue 13 (14th September 2020) - Malekian, Kaveh; Safargholi, Farhad; Schufft, Wolfgang; Dreyer, Thomas; Cassoli, Jair; Adloff, Stephan; Ackermann, Florian; Moghadam, Hasanali; Rogalla, Soenke; Kaatz, Gesa; Meyer, Marc Florian; Mueller, Sascha; et al.
Abstract : This study addresses the validation of harmonic models for power generation units considering practical aspects associated with test‐bench and on‐site measurements. A new method is proposed for the harmonic model validation. This method has been developed within the joint research project 'NetzHarmonie, ' which deals with the study of harmonic emissions of renewable energy sources in the power system. The main idea for model validation is to compare the harmonic voltage–current characteristic of the model with the measured harmonic voltage–current pairs. This idea is implemented in a practical process by considering measurement uncertainties as well as the time variation of harmonics. In the validation process, measurement data should meet the given requirements to verify whether they are suitable for the task of validation. The application of the proposed model validation process to photovoltaic and wind power generation units with different topologies and power classes is thoroughly addressed as well. The application of the proposed process is illustrated in detail for selected harmonic orders from these measurement campaigns. This study aims to provide a scientific foundation for the consideration of the harmonic model validation of power generation units in future standards.